HO CHI MINH'S VIEW ON SOCIAL SECURITY AND ITS MEANING FOR VIETNAM - Tuan Anh, Tran (Perkumpulan Dosen Program Hibah Indonesia, 2023)
In Ho Chi Minh's ideological framework, his perspectives on social security were consistently evident throughout his revolutionary endeavors. Rooted in his philosophy of life and the principles of cherishing and respecting the people, Ho Chi Minh's stance on social security emerged as a product of his enduring commitment to revolutionary activities. In his collaborative efforts with the Party to guide the revolution, Ho Chi Minh consistently emphasized trust in the people, respect for their dignity, and reliance on the formidable strength of the populace. Consequently, his focus remained steadfastly on realizing tangible and justifiable benefits for the people. Drawing inspiration from Ho Chi Minh's viewpoint, the Communist Party of Vietnam has put forth and steered the implementation of social security policies aimed at ensuring the provision of sufficient sustenance, warm clothing, and rightful entitlements for the people. Within the scope of this discourse, the author concentrates on exploring Ho Chi Minh's fundamental perspectives on social security, as well as examining how the Communist Party of Vietnam applies these principles in formulating and executing social security policies in contemporary society.